1997
DOI: 10.1021/jp963837i
|View full text |Cite
|
Sign up to set email alerts
|

Transient Absorption Spectra of Photoconductive Polyimides and Their Model Compound by Picosecond Pulse Radiolysis

Abstract: Transient absorption spectra of an aromatic polyimide, PI(PMDA/ODA), and a polyimide with an alicyclic diamine, PI(PMDA/DCHM), were determined in order to investigate the main active species in the photoconductivity of the polyimide films by picosecond pulse radiolysis method. A model compound, N,N′di-n-butylpyromellitic diimide (DBPMDI), was utilized to investigate the active species of pyromellitic imide moieties in solutions of dichloromethane (DCM) and tetrahydrofuran (THF). In the aromatic polyimide film,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
(46 reference statements)
0
15
0
Order By: Relevance
“…Unfortunately, it is quite difficult to predict a priori the imidization temperature optimum which leads to the best electrical properties. Literature presents a large range of imidization temperature from 200 °C to 425 °C without always indicating if it corresponds to an optimum [6,[18][19][20][21][22][23]. Moreover, these works present mainly the optimization of the imidization reaction from a chemical point of view only based on qualitative infrared measurements.…”
Section: Synthesis and Optimization Of The Imidization Of Bpda-pda Pomentioning
confidence: 99%
“…Unfortunately, it is quite difficult to predict a priori the imidization temperature optimum which leads to the best electrical properties. Literature presents a large range of imidization temperature from 200 °C to 425 °C without always indicating if it corresponds to an optimum [6,[18][19][20][21][22][23]. Moreover, these works present mainly the optimization of the imidization reaction from a chemical point of view only based on qualitative infrared measurements.…”
Section: Synthesis and Optimization Of The Imidization Of Bpda-pda Pomentioning
confidence: 99%
“…6, 17,18 To investigate the intra-or intermolecular interaction of the polyimide with the alicyclic diamine, PI(PMDA/DCHM), UV absorption spectra were observed first using a model system (CPD). Figure 2 shows absorption spectra of the model compound acid)s was converted to the polyimides, which was ascertained by IR spectroscopy.…”
Section: Formation Of Weak Intermolecular Interaction In the Ground Smentioning
confidence: 99%
“…matic hydrocarbons in aromatic amine solvents by measuring the fluorescence spectra reported Photoconduction mechanism of PI(PMDA/ by Mataga et al 39,40 They have reported that the ODA) film is well known to be due to the chargeabsorption spectra of the hydrocarbons in the transfer complex formed between pyromellitic imamines do not show any essential change, but speide moiety and diphenyl ether group in the ground cific interaction between a hydrocarbon and an state both intra-and intermolecularly. 6,17, 18 We 18 amine occurs only in the electronically excited have investigated the charge carriers in the phostate (the fluorescent state). It has been clearly toconductivity of PI(PMDA/ODA) film by using demonstrated from the relationship among the a picosecond pulse radiolysis method, reporting a frequencies of the long wavelength fluorescence, radical cation of diphenyl ether moiety at 550 nm the electron affinities of the excited-state aroand radical anions of pyromellitic imide moiety matic hydrocarbons, and the ionization potentials at 660 and 720 nm by electron transfer from the of the amines, that the interaction can be ascribed aromatic ring to imide moiety in the polymer to the charge transfer from the amine to the exbackbones.…”
Section: Molecular Packing Dependence Of the Photoconductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Judging from the result of pulse radioly model compounds in solution, the long-lived intermediate at 720 nm is assigned to radical anion of the electron-accepting pyromellitic imide moieties in the aromatic PI films [8]. The other peaks at 420 and 600 nm decayed simultaneously within 3 hours.…”
mentioning
confidence: 98%